In Vitro Susceptibility of Mycobacterium ulcerans Isolates to Selected Antimicrobials. (14th March 2017) - Owusu, Enid; Newman, Mercy J.; Addo, Kwesi K.; Addo, Phyllis
Abstract : Background. The current definitive treatment of Buruli ulcer with antibiotics makes the issue of antimicrobial drug resistance an unavoidable one. This is as a result of drug misuse by health personnel and patients' noncompliance to treatment regimen. Monitoring of these factors and screening for new effective antimicrobials are crucial to effective management of Buruli ulcer disease. This study therefore investigated the inhibitory activity of some antibiotics against isolates of Mycobacterium ulcerans . Methods. Activity of eight antibiotics was tested against twelve M. ulcerans isolates (2 reference strains and 10 clinical isolates). The anti- M. ulcerans activities were determined by the agar dilution method and the minimum inhibitory concentrations (MICs) were determined by the agar proportion method. Results. All antimicrobials investigated had activity against M. ulcerans isolates tested. The MICs ranged from 0.16 μ g/mL to 2.5 μ g/mL. Azithromycin recorded the highest inhibitory activity at a mean MIC of 0.39 μ g/mL, whilst clofazimine a second-line antileprosy drug, recorded the lowest at a mean MIC of 2.19 μ g/mL. Among the four antituberculosis drugs, rifampicin had the highest activity with a mean MIC of 0.81 μ g/mL. Conclusion. Azithromycin could be considered as a lucrative alternative to existing treatment methods for inhibiting M. ulcerans in Ghana.